Descending control in sensitization of reflexes in the rat - Dobson, Katharine L. (2013)
Electrical stimulation of the heel or toes evokes short latency polysynaptic reflexes in muscles of the ankle extensor medial gastrocnemius (MG), the ankle flexor tibialis anterior (TA) and the knee flexor biceps femoris (BF), the co-ordinated actions of which form an organized protective withdrawal response. Previous studies in the rabbit have shown that such reflexes are enhanced (sensitized) or inhibited by application of the chemogenic agent mustard oil (MO) to various areas of the body surface in a manner that reinforces the protective function of these responses. The organization of these ‘sensitization fields’ was strictly controlled by supraspinal pathways from the brain. The aim of the present experiments was therefore to extend these studies of the spatial organization of sensitization of withdrawal reflexes into the rat, the species most commonly used in pain research.